Soil Mesofauna Response to Cover Crops and Mycorrhizal Inoculated Plantation on Limestone Quarry Revegetation - Retno, Retno Prayudyaningsih (Forestry Department, University of Muhammadiyah Makassar, 2016)
Cover crops establishment followed by mycorrhizal inoculated tree plantation accelerate limestone quaryy restoration. Soil mesofauna is a useful indicator for assessing biodiversity recovery, as they are sensitive to human disturbance and involved in ecological processes. In this research, soil mesofauna presence used to evaluate limestone quarry restoration by cover crops and mycorrhizal inoculated tree esatblisment. Soil mesofauna are measured using individual density, species diversity, richness and important value. The study was conducted in four types of areas on limestone postmining lands are open areas/natural conditions without planting, cover crop area, non mycorrhizalinoculated plant area and mycorrhizal-inoculated plant area. The result showed The higher individual density, diversity and species richness of soil mesofauna on cover crops and mycorrhizal inoculated plant area than other areas are indicators of limestone quarry restoration rate. Furthermore the presence of Formicidae family that dominated on cover crops and mycorrhizal inoculated plant area, and emergence of Acari group only on mycorrhizal inoculated area also an indicator of limestone quarry restoration.